(untitled) (Signifiances (Signifying), 2017)
This paper lays some foundations for a method of enactive lexicology by applying the postulates of enaction at the submorphological level following Bottineau (2008, 2010, 2012a, b). We use the theory of submorphemic saliencing (Author 2012a, 2014a,b; 2015), which postulates that only one of the signifier’s characteristics is exploited for a given word according to synchronic events and utterances. The enaction of form and meaning underpinned by this saliencing process therefore involves the activation of one part and the inhibition of the rest of the morphology, analogously to muscular and neural functions. It is also a phenomenon that is at once « perc-active », simplex and vicarious according to the definitions of Berthioz (1997, 2009, 2013).